1998
DOI: 10.1046/j.1464-410x.1998.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenocarcinoma of the urinary bladder:

Abstract: Objective  To evaluate the outcome after the treatment of primary non‐urachal vesical adenocarcinoma and to determine the significant prognostic factors. Patients and methods  The records of 185 patients with vesical adenocarcinoma were reviewed. The pathological evaluation included the determination of pathological stage, tumour grade, presence or absence of mucin and its location, evidence of bilharzial infestation and flow‐cytometric DNA analysis. The mean follow‐up of the treated patients was 3.1 years. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
72
5
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 41 publications
12
72
5
4
Order By: Relevance
“…2,3,[7][8][9] In 1 of the larger series reporting on both types, there was a trend toward improved survival in subjects with urachal adenocarcinoma, although it did not reach statistical significance (P ¼ .07). 3 In that series of 24 urachal and 48 nonurachal tumors, the 5-year survivals were 61% vs. 31%, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…2,3,[7][8][9] In 1 of the larger series reporting on both types, there was a trend toward improved survival in subjects with urachal adenocarcinoma, although it did not reach statistical significance (P ¼ .07). 3 In that series of 24 urachal and 48 nonurachal tumors, the 5-year survivals were 61% vs. 31%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The higher rate reported from single institutions specializing in urologic oncology likely reflects the referral pattern of these rare tumors, rather than the true relative incidence of urachal and nonurachal adenocarcinomas. el-Mekresh et al 8 reported the largest series on primary bladder adenocarcinoma from Egypt, where bilharziasis is endemic and is associated with a higher risk of bladder adenocarcinomas. Whereas adenocarcinomas account for less than 2% of all bladder cancers in most series, 10% of all bladder cancers in the el-Mekresh et al report were adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent genomic data have described a basal/squamous-like molecular subtype that has squamoid morphology and immunophenotype and is associated with poor survival and poor response to systemic therapy [69,70]. Glandular neoplasms constitute the second most common form of divergent differentiation, seen in up to 18% of invasive tumours and defined by the presence of gland formation [71][72][73]. These tumours commonly have enteric features and, in isolation, can be easily confused with colonic adenocarcinoma.…”
Section: Invasive Urothelial Carcinoma With Divergent Differentiationmentioning
confidence: 99%
“…Progressive invagination of hyperplastic epithelial buds into the lamina propia (Von Brunn's nest) leads to the formation of cystitis cystica. Subsequent, metaplasia of the urothelial lining to these cyst to columnar mucin-producing cells results in the production of cystitis glandularis, which is premalignant lesion 2 . Alternatively, cuboidal or columnar metaplasia of the surface epithelium can occur with no downward invagination, Chronic vesical irritation and infection are the predisposing factors of theses changes.…”
Section: Discussionmentioning
confidence: 99%